KARAKTERISASI MEMBRAN FILTRASI DARI KHITOSAN DENGAN BERBAGAI JENIS PELARUT - Nastiti Siswi Indrasti, Suprihatin dan Feny Silvia (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTMembrane is a semi-permeable thin layer that can be used to separate components by holding and flowing certain component through pores. The performance of membrane is often evaluated by two parameters, namely flux and rejection. The objective of the paper is to present characteristics of chitosan membrane made using various chitosan solvents and chitosan concentrations. Experimental results showed that rendement of chitosan from shrimp shell was 15.3% with mouisture of 5.5% and ash content of 0.72%. Membrane made using formic acid and chitosan concentration of 7% yielded the highest flux of 285 L/m2h for clean water, flux 52 l/m2h for albumin solution, 144 L/m2h for starch suspension, and 222 l/m2h for glucose solution. The highest rejection was achieved by membrane made from acetic acid with chitosan concentration of only 27 percent for albumine solution. Key words: membrane filtration, chitosan